Rancang Bangun Sistem Informasi Berbasis Website Sebagai Media Informasi dan Pengarsipan Dokumen pada Forum Anak Kecamatan Tigaraksa (FATIGAS) - Sultan Alif Syahbana; Sulthan Ghatfan Naufal Abbad; Bima Pratama Setiawan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Data management and information dissemination in community organizations in the digital era often face efficiency barriers when relying on conventional methods or non-integrated third-party platforms. The Tigaraksa District Children's Forum (FATIGAS), as a highly active child aspiration platform, faces significant challenges in publishing organizational profiles and archiving legality documents, such as Decrees (SK), which are currently still based on a "one gate system" via external storage media. This condition causes obstacles to operational mobility and data accessibility delays for organization members. This research aims to design and build a web-based information system that integrates activity publication media with a centralized and efficient digital document repository system. Software development is carried out by applying the Agile Software Development method, which allows for an iterative, flexible, and adaptive development process to the dynamic needs of the organization through systematic sprint cycles. The system architecture is built using the modern Node.js platform with the Express JS framework on the server side, as well as utilizing MySQL as a database management system to ensure data integrity. Administrative access security is strengthened with JSON Web Token (JWT) technology and the HMAC-SHA256 algorithm to guarantee the confidentiality of the authentication process. The results of functional testing using the Blackbox Testing method show that all main modules, from activity content management to archive downloads, run according to the functional requirements. The implementation of this system has successfully provided a professional integrated information center while eliminating internal bureaucratic barriers in processing FATIGAS digital archives.